Workplace Spirituality dan Leader-Member Exchange Terhadap Organizational Citizenship Behavior dimediasi oleh Kepuasan Kerja - Ulandari, Riri; Suryosukmono, Gerry (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
This research aims to examine the influence of workplace spirituality and leader-member exchange on organizational citizenship behavior mediated by job satisfaction in Public Works and Spatial Planning (PUPR) Prov. Bengkulu. This study uses a quantitative approach. The population in this study were all employees of the Provincial Public Works and Spatial Planning (PUPR). Bengkulu consisting of 235 respondents. The data source in this research is primary data obtained through distributing questionnaires to the research population. The analysis method used is SEM-PLS. The results of this research show that workplace spirituality influences organizational citizenship behavior. Leader-member exchange influences organizational citizenship behavior, job satisfaction influences organizational citizenship behavior. workplace spirituality influences job satisfaction, leader-member exchange influences job satisfaction. Workplace spirituality influences organizational citizenship behavior, mediated by job satisfaction. Leader-member exchange influences organizational citizenship behavior, mediated by job satisfaction.